KRISTIJONAS DONELAITIS HAD A PERSONAL LIBRARY, HAD HE NOT ? - KAUNAS, DOMAS (Knygotyra, 2015)
The object of research is a personal library of Kristijonas Donelaitis. Its investigation has not produced any results so far. This depends on the low relevance of the problem and scarce source data available. This article suggests that it is necessary to broaden and increase the sets of historical data needed for the analysis of the problem and their variety. It is also important to use new methods and critical approach to the evaluation of the sources and historiographic literature used by the creators of Donelaitis’ studies such as Martin Ludwig Rhesa, Ludwig Loui Passarge, Franz Oskar Tetzner, Aleksandr Horn, Carl Wilhelm Hugo Freyberg). Taking into account the present state of historiography, the aim of the research is formulated as follows: to assertain, to deny, or to leave open the possibility of the existence of the personal library of Donelaitis for further investigation until its reality or at least the fact of probability to be answered unambiguously. The grounds for this research were found in the ambition of the Prussian royal authorities of the 18th century to impose more stringent control on the knowledge, skills and personal life of Protestant priests. Back then, rather fruitful means were used to accomplish this goal. The priests had to react to the new developments in order to improve their official and social standing. This led to the acquisition of a handy library for the development of skills and education. When investigating the library of Donelaitis the main aims should be as follows: 1) to identify personal and official information and creative needs of its owner, 2) to establish the means and sources of library acquisition, 3) to identify its composition and purpose, 4) to trace its fate after the death of the owner. The method applied is based on theoretical proofs and the speculative analysis of historiographical statements and secondary sources. At present, the conducted investigation allows us to provide only theoretical assumptions. According to the results, no convincing proof of the existence of Donelaitis’ personal library can be produced. The possibility of the denial of its existence still exists. Therefore, we can formulate the following dualistic conclusion: 1) according to the conditions of the time and his position, Donelaitis must have had a personal library, 2) so far, there is no data about the fact of the existence of this library.